Study on Morphometric, Meristic and Growth Patterns of Osteochilus wandersii from the Rokan Kiri River, Rokan Hulu Regency, Riau Province - Abdullah Hamid; Windarti '; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Osteochilus wandersii or lelan fiah is freshwater fish that inhabit the Rokan Kiri River. This fish has high economical value, around Rp 30.000-50.000/Kg. Information on biological aspects of this fish, including the morphometric and meristic, however, is rare. To understand the morphometrical, meristical characteristics and growth pattern of this fish, a research had been conducted from November to December 2014. There were 116 fishes (66-185 mm SL and 5.39-143.13 gr BW) captured from the Rokan Kiri River. There were 26 morphological characteristics measured and 10 meristical characteristics counted. Results shown that all of morphometrical characteristics were almost isometric as the fish growing. The meristical characteristic of the fish were as follow: D.2.101/2-121/2; P.1.14-15; V.1.8; A.1.41/2; C.2.17, the number of scale in the pre-dorsal fin was 10-11, lateral line scale was 33-36, around the body was 27-29 and around the caudal peduncle was 14-16. The Lenght-weight relationship shown that the growth of male and female fish was isometric (b = 3.09). The water quality parameter shown that temperature 25-28 °C, transparency 12-40 cm, pH 6, DO 4.7-6.48 mg/l, CO2 17.97-27.96 mg/l, and current speed 0.327-0.625 m/s. Data on water quality parameters indicate that water quality in the Rokan Kiri River is able to support the life of the lelan fish.Keywords : Osteochilus wandersii, Rokan Kiri River, morphometric, meristic, growth patterns